Examining Travel Motivations of International Tourists to Amritsar - Chakravarty, Anuradha; Bhinder, Dr. Hardaman Singh (The journal of contemporary issues in business and government, 2022)
To address the scarcity of research concerning the constituents of travel motivations of International tourists to the city of Amritsar in Punjab (India), the present study collected a data of 282 International tourists and used Dann’s push-pull motivational typology. Factor analysis uncovered six travel motivations: Escape from routine and relaxation, fulfilling spiritual needs knowledge seeking, destination attributes, accessibility and entertainment activities to visit Amritsar. The findings reveal that the main motivation of the International tourists was the spectacular Golden Temple along with the cultural and historical attractions and the escape from routine for relaxation remained a major push motive. The findings also provides insights to the tourism authorities of Amritsar about various pull and push motivations and recommends that the service providers and the destination managers in this most visited place of Punjab must ensure tourists satisfaction in order to increase repeat visits and make it the most prized destination among the tourists all across the World.